Setup a remote Kubernetes environment. - Deza, Alfredo (Pragmatic AI Solutions, 2021)
Develop with Kubernetes without having a running cluster locally using an SSH tunnel to connect to the remote K8s instance and then use regular kubectl commands to interact with the cluster. Then, supercharge your k8s flows with k9s, a powerful interface in the terminal for k8s In this video I'll walk you through some useful techniques you can use to setup a remote k8s cluster that runs locally, and will then use k9s, a powerful terminal UI that allows you to control a kubernetes cluster easily with less commands. Topics include: Connect to a remote K8s cluster over SSH using a tunnel Use different SSH flags when creating an SSH tunnel Learn k9s, a powerful terminal UI to control Kubernetes Useful links: * Github Gist with instructions * k9s CLI Tool.